2015
DOI: 10.1177/0957650915571954
|View full text |Cite
|
Sign up to set email alerts
|

Numerical research on the mixing mechanism of lobed mixer with inlet swirl in linear radial distribution

Abstract: A detailed numerical simulation is presented to investigate the effects of inlet swirl and its radial distribution on the mixing mechanisms of a turbofan mixer with 12 lobes, by using the commercial ANSYS CFX solver and k-! SST model. The core-to-bypass temperature ratio and pressure ratio were set to 2.59 and 0.97, respectively, giving the Mach number of 0.66 and bypass ratio of 2.65 at mixing nozzle outlet. In the core inlet, the swirl angle was raised from 0 to 30 in a uniform or linear radial distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…As a result, they suggested that turbine systems should be carefully designed to eliminate swirling flow at the outlet of low-pressure turbines (LPT). The authors' team conducted a series of studies [18][19][20][21][22][23][24][25] to understand the flow mechanism in lobed mixers under inlet swirl conditions. They found that the inlet swirl could introduce an additional streamwise vortex that improved the jet mixing.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they suggested that turbine systems should be carefully designed to eliminate swirling flow at the outlet of low-pressure turbines (LPT). The authors' team conducted a series of studies [18][19][20][21][22][23][24][25] to understand the flow mechanism in lobed mixers under inlet swirl conditions. They found that the inlet swirl could introduce an additional streamwise vortex that improved the jet mixing.…”
Section: Introductionmentioning
confidence: 99%